THE ROLE OF DATUK ABDUSSALAM IN THE SPREAD OF ISLAM IN TIMBANG LAWAN VILLAGE, LANGKAT REGENCY IN 1590-1620: Peran Datuk Abdussalam dalam Penyebaran Islam di Desa Timbang Lawan Kabupaten Langkat Tahun 1590-1620 - Berliana Wulan Dari; Yusra Dewi Siregar (SOSIOEDUKASI, 2025)
The spread of Islam in the archipelago took place gradually and involved various important figures, including Sheikh Abdus Salam or Datuk Landak. A cleric from Malaysia who settled in Timbang Lawan Village, Langkat Regency in the 15th century AD. He played an important role in inviting the local community to embrace Islam through a spiritual approach and the Naqshbandiyah order. This study began with the following problems: (1) how did Islam enter Timbang Lawan Village, (2) what was the role of Sheikh Abdussalam in spreading Islam in the area, and (3) what are his legacies and influences on the religious life of the local community. The purpose of this study is to answer the third question through a qualitative descriptive historical and sociological approach. The methods used include observation, interviews, literature studies and documentation of secondary sources in this study including journals and books that support this research. This research is expected to contribute to scientific studies of local Islamic history in Indonesia. The results of the study show that the people of Timbang Lawan Village greatly appreciate the cultural heritage left by Sheikh Abdussalam, such as the tomb of the Sheikh himself. Until now, the local people still greatly appreciate his legacy.